PIERCING THE CORPORATE VEIL TOWARD HOLDING COMPANY RESPONSIBILITY IN THE PERSPECTIVE OF ISLAMIC JUSTICE - ines prasheila kusmastuti (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2024)
Decision Number 89/PK/Pdt/2010 shows that business relationships do not always run smoothly. In the verdict, PT Effem Foods Inc as the holding company is jointly and severally liable to PT Smak Snak for the unlawful act of PT Effem Indonesia as the subsidiary company. The research method used is normative juridical using a case law approach. The purpose of this study is to explain the basis of the judge's consideration in deciding the judicial review case number 89/PK/PDT/2010 related to the application of piercing the corporate veil against PT Effem Foods Inc and reviewed from the concept of al-'Adl. The results showed that the consideration of judges in the Supreme Court Decision Number 89/PK/Pdt/2010 related to the application of piercing the corporate veil against PT Effem Foods Inc was appropriate and in accordance with Law Number 40 of 2007 concerning Limited Liability Companies and the Civil Code because PT Effem Foods Inc was proven to have committed illegal acts. The judge's decision in applying piercing the corporate veil against PT Effem Foods Inc is in accordance with the concept of al-'Adl which means fair in the same sense because PT Effem Foods Inc and PT Effem Indonesia both committed illegal acts and there are no rules related to the division of the amount of joint liability on the holding and subsidiary companies.